2019
DOI: 10.5194/acp-2019-410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Characterization of Organosulfates in Arctic Ocean and Antarctic atmospheric aerosols

Abstract: <p><strong>Abstract.</strong> Organic aerosols are ubiquitous components of atmospheric aerosols. Organosulfate aerosols have been detected in the Arctic Ocean atmosphere and may play an important role in the radiative balance in Polar Regions. Aerosol samples from the Arctic Ocean and Antarctic atmosphere during 2014/2015 CHINARE were analysed by ultrahigh resolution mass spectrometry coupled with negative ion mode electrospray ionization (ESI(-)-UHRMS). Hundreds of organic compounds were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Previous PON observations in the urban and rural areas of China have demonstrated that there is a significant variation in PON abundance and concentrations range from below detection limits to several micrograms per cubic meter [17,[25][26][27][28][29]. PON abundance varies markedly by season and location owing to the effects of natural conditions and anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous PON observations in the urban and rural areas of China have demonstrated that there is a significant variation in PON abundance and concentrations range from below detection limits to several micrograms per cubic meter [17,[25][26][27][28][29]. PON abundance varies markedly by season and location owing to the effects of natural conditions and anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%
“…PONs ranging from below detection limits to several micrograms per cubic meter found that mixed urban fossil fuel combustions were primarily responsible for the high concentrations of PONs in southern California. On the basis of latest observations of PONs in China, large disparity exist and the concentrations of PONs range from below detection limit to several micrograms per cubic meter (He et al, 2014;Ma et al, 2014;Zhang et al, 2016;Li et al, 2018;Ye et al, 2019). suggested that future reduction in anthropogenic emissions would help to reduce the 70 biogenic SOA loading because the abundances of organosulfates and nitrooxy-organosulfates increased significantly in acidic sulfate aerosols under high humidity.…”
Section: Introductionmentioning
confidence: 99%